Enhancing Interfacial and Mechanical Properties of Carbon Fiber/Poly (Ether Ether Ketone) Composites via Bisphenol-Based Polyimide Modification - Albayrak, Aylin; Dogu, Mustafa; Cakir, Mustafa; Turhan, Kadir (MDPI, 2025)
This study focuses on the synthesis of two new bisphenol-based polyimide (PI) sizing agents to improve the fiber-matrix interface of carbon fiber-reinforced poly (ether ether ketone) (CF/PEEK) composites. One of the synthesized polyimides contains bisphenol A (BPA) monomer, while the other has bisphenol S (BPS) monomer. The produced polyimide precursor resins were coated with carbon fibers by thermal imidization. The thermal, thermomechanical, and mechanical properties of the CF/PEEK composites produced by the autoclave process were investigated. According to the mechanical test results, there was a balanced performance between the BPS-containing polyimide-coated composites (CF-PEEK-PI-S) and the BPA-containing polyimide-coated composites (CF-PEEK-PI-A). While tensile strength is 291 MPa and interlaminar shear (ILSS) strength is 119 MPa, the CF-PEEK-PI-A sample showed superior mechanical properties in flexural (92.1 MPa) and compressive strength (54.9 MPa). As a result, it was concluded that bisphenol-based polyimide coatings significantly improve the interfacial interactions in CF/PEEK composites, which have great potential in aerospace, automotive and advanced engineering applications.
Keywords: carbon fiber composites; bisphenol-based monomers; polyimide sizing; poly (ether ether ketone); interfacial adhesion; IMPACT BEHAVIOR; ADHESION; Polymer Science